Restricting Reasons: A New Battleground in Abortion Regulation - Will, Jonathan F. (The Hastings Center report, 2020)
The latest trend in abortion restrictions in the United States targets a woman's reasons for terminating a pregnancy. Fourteen states have attempted to enact laws prohibiting abortion on the basis of fetal sex, race, and/or genetic anomaly. These laws are different from regulations tied to a government interest in protecting women's health. Laws that restrict reasons implicate a different set of government interests to be weighed against a woman's constitutional right first recognized in Roe v. Wade. These laws also seek to reframe the nature of the right asserted by the woman. To date, the Supreme Court has declined to address the constitutionality of laws that restrict reasons, and the Court's most recent abortion decisions provide little guidance. It is possible that a conservative majority of the Supreme Court would uphold a law that prohibits reasons for having an abortion that appear discriminatory. But such laws would be difficult to enforce and therefore may be relegated to policy statements rejecting discriminatory norms as opposed to being effective means of restricting access to abortion.